FAKTOR-FAKTOR YANG MEMPENGARUHI PROSES DITETAPKANNYA RANPERDA PENETAPAN NEGERI DI KABUPATEN SERAM BAGIAN BARAT - TAMALENE, SEHE; NATANIEL, ELAKE (Patria Artha Management Journal, 2024)
This research aims to find out the process and stages of preparing the Draft Regional Regulation (Ranperda) Determining the State of West Seram Regency and to find out thecauses of delays in the process of enacting the Ranperda. This type of research isqualitative and uses data collection techniques using interviews, observation,documentation and literature review. The results of this research show that the factors thathinder the enactment of the Draft Regional Regulation for Determining the State of WestSeram Regency into a Regional Regulation for Determining the State are the fear of openconflict between fellow citizens internally, the occurrence of conflict between one countryand another country whose customary rights directly border it, determining the coordinatesof state borders, there are several villages that have state status, there are unhealthy gamesboth within the DPRD and the West Seram Regency government, and the regionalboundaries between a state and a village have not been regulated.